AN ANALYSIS OF RACISM IN THE FILM OF THE GREEN MILE BY FRANK DARABONT - Nellu Atika; Rezky Khoirina Tarihoran (PHILOLOGY Journal of English Language and Literature, 2022)
This research analyzes the forms of racism in the film The Green mile by Frank Darabont. The Green Mile tells about the experience of a warden who has a prisoner who comes from black people and has magical powers within him. This research shown the treatment of racist forms experienced by minorities. The purpose of this research is first, to find out the types of racism found in the movie. Second, to find out the resistance shown in the movie. This study uses a semiotic approach by Charles Sanders Pierce. The method used is descriptive qualitative method to analyze the data in this research. The data sources are taken from dialogues and scenes in the film The Green Mile by Frank Darabont. The finding in the research are first, kinds of racism that occur in the green mile films are internalized racism, interpersonal racism, and institutional racism. Second, the resistance that shown in The Green Mile films are closed resistance and open resistance.